Digitalizing Community Health Work: A Struggle over the Values of Global Health Policy - Tine Hanrieder; Eloisa Montt Maray (Historical Social Research, 2021)
The introduction of digital technology has sparked new debates about the value of community health workers in low- and middle-income countries. This debate offers important insights into the conventions that are relevant in global public health. Community health workers, a workforce that was already celebrated during the 1970s Primary Health Care movement, are having a remarkable revival in recent years, and myriad actors seek to boost their impact through mobile devices. Our content analysis of the public health literature evaluating this impact reveals the centrality of attempts at reconciling equity and cost effectiveness concerns, and thus considerable normative tensions. Additionally, we find that discussions about “domestic” values such as privacy and gender roles come with a paternalistic undertone, calling for feminist and postcolonial engagement with the digitalization of community health work.
Keywords: 300; global health; primary health care; community health worker; feminism; orders of worth; economics of convention; mobile health; low- and middle-income countries; policy; values; global south; mHealth